Association of rs11643718 SLC12A3 and rs741301 ELMO1 Variants with Diabetic Nephropathy in South Indian Population. (4th October 2016) - Bodhini, Dhanasekaran; Chidambaram, Manickam; Liju, Samuel; Revathi, Balakannan; Laasya, Dhandapani; Sathish, Natarajan; Kanthimathi, Sekar; Ghosh, Saurabh; Anjana, Ranjit Mohan; Mohan, Viswanathan; Radha, Venkatesan
Summary: This study reports on the association of genetic variants selected from previous genome‐wide association studies for type 2 diabetic nephropathy in south Indians. Eight variants were genotyped in 601 type 2 diabetic subjects without nephropathy (DM) and 583 type 2 diabetic subjects with nephropathy (DN) by MassARRAY. The minor allele frequencies of rs11643718 SLC12A3 variant and rs741301 ELMO1 variant were significantly different between DM and DN groups ( P = 0.029 and 0.016, respectively). A combined analysis showed that the subjects carrying the risk genotypes of both these variants (GG of rs11643718 + AG/AA of rs741301) had a significant association with DN with an odds ratio [adjusted for age, sex, Body Mass Index (BMI), HbA1c, and systolic Blood Pressure (BP)] of 1.73 (1.30–2.30, P = 1.72 × 10 –4 ) as compared to subjects carrying all other genotype combinations. This is the first study to report a significant association of the SLC12A3 rs11643718 and ELMO1 rs741301 (Single nucleotide Polymorphism) SNPs with diabetic nephropathy in south Indians.